Transcriptome analysis reveals anthocyanin regulation in Chinese cabbage (Brassica rapa L.) at low temperatures - Dai, Yun; Zhang, Lei; Sun, Xiao; Li, Fei; Zhang, Shifan; Zhang, Hui; Li, Guoliang; Fang, Zhiyuan; Sun, Rifei; Hou, Xilin; Zhang, Shujiang (Scientific reports, 2022)
Chinese cabbage that prefers cold conditions is also affected by low-temperature stress, such as the accumulation of leaf anthocyanins. Research on anthocyanin biosynthesis and regulation mechanisms has made great progress. However, research on anthocyanin accumulation for resistance to biological and non-biological stress is still lacking. To study the relationship between anthocyanin accumulation of Chinese cabbage and resistance under low-temperature conditions, RNA sequencing (RNA-seq) was performed on Chinese cabbage ‘Xiao Baojian’ grown at a low temperature for four time periods and at a control temperature for five time periods. In Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, 7954 differentially expressed genes (DEGs) were enriched, of which 587 DEGs belonged to "biosynthesis of other secondary metabolites." Gene temporal expression patterns were used to discover enriched genes related to phenylpropanoid biosynthesis; flavonoid biosynthesis and anthocyanin biosynthesis pathways were found in cluster 1. The interaction networks were constructed, and hub genes were selected, showing that flavonoid biosynthesis pathway genes ( DFR , ANS , F3H , FLS1 , CHS1 , CHS3 , and TT8 ) and defense mechanisms-related genes ( DFR , SNL6 , and TKPR1 ) interact with each other. Anthocyanin biosynthesis DEGs in Chinese cabbage were evaluated under low-temperature conditions to map the relevant pathways, and expression maps of transcription factors in the flavonoid pathway were created at various periods. Low temperature upregulated the expression of genes related to anthocyanin biosynthesis. Taken together, our results provide further analysis of the relationship between plant anthocyanin synthesis and stress resistance and may also provide further insights for the future development of high-quality color and cold-tolerant Chinese cabbage germplasm resources.